PIDANA PENGAWASAN SEBAGAI PENGGANTI PIDANA BERSYARAT MENUJU KEADILAN RESTORATIF (CRIMINAL CONDITIONAL SUPERVISION AS A SUBSTITUTE OF PROBATION SENTENCE TOWARDS RESTORATIVE JUSTICE) - Puteri Hikmawati (Jurnal Negara Hukum: Membangun Hukum Untuk Keadilan, 2016)
Probation sentence stipulated in the Criminal Code provide less protection to perpetrators of criminal acts because it is not a type of sanctions, but how to act a sanction. Therefore, the Criminal Code Bill regulate criminal conditional supervision as a new type of criminal sanctions in the principal criminal. Criminal conditionalsupervision of a substitute and alternative criminal imprisonment. This article analyzes the implementation of the conditional criminal and penal supervision regulations in the Bill, and also describes the implementation of criminal supervision in some countries, so that a restorative justice can be realized. Criminal supervision regulations in the Bill resembles a probation system in the UK, but stressed indemnification arising from criminal acts. In criminal punishment supervision to note the rights of victims and human resources prepared Correctional Center of Ministry of Law and Human Rights as a supervisory agency and the supervisory judge, as well as facilities and infrastructure. ABSTRAKPidana bersyarat yang diatur dalam KUHP kurang memberikan pelindungan kepada pelaku tindak pidana karena bukan merupakan jenis pidana tetapi cara menjalankan pidana. Oleh karena itu, RUU KUHP mengatur pidana pengawasan sebagai jenis sanksi pidana baru dalam pidana pokok. Pidana pengawasan merupakan pengganti pidana bersyarat dan alternatif pidana penjara. Artikel ini mengkajipelaksanaan pidana bersyarat dan pengaturan pidana pengawasan dalam RUU KUHP dengan melihat pelaksanaan pidana pengawasan di beberapa negara, agar keadilan restoratif dapat terwujud. Pengaturan pidana pengawasan dalam RUU KUHP menyerupai sistem probation di Inggris, tetapi menekankanpengembalian kerugian yang ditimbulkan dari tindak pidana. Dalam penjatuhan pidana pengawasan perlu diperhatikan hak-hak korban dan dipersiapkan sumber daya manusia Balai Pemasyarakatan Kemenkumham sebagai lembaga pengawas dan hakim pengawas, serta sarana dan prasarana.